2009
DOI: 10.1186/1472-6963-9-212
|View full text |Cite
|
Sign up to set email alerts
|

The politics of local hospital reform: a case study of hospital reorganization following the 2002 Norwegian hospital reform

Abstract: BackgroundThe Norwegian hospital reform of 2002 was an attempt to make restructuring of hospitals easier by removing politicians from the decision-making processes. To facilitate changes seen as necessary but politically difficult, the central state took over ownership of the hospitals and stripped the county politicians of what had been their main responsibility for decades. This meant that decisions regarding hospital structure and organization were now being taken by professional administrators and not by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
5
2
Order By: Relevance
“…Increases in induced demand were presented as a weakness in the evidence examined. However, one of the present study's strengths was that it included expert opinions of the government structure, which contradicted the results of similar studies (11)(12)(13)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Increases in induced demand were presented as a weakness in the evidence examined. However, one of the present study's strengths was that it included expert opinions of the government structure, which contradicted the results of similar studies (11)(12)(13)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussioncontrasting
confidence: 69%
“…2021; 10(2):e112125. cept in designing a comprehensive and efficient evaluation system, were inconsistent with the findings of the studies, but in this study, experts announced that the development of performance evaluation indicators for monitoring public hospitals was not found in the studies (9,13,25,30). Zhao and Zhang (2018), in their qualitative study conducted through interviews with experts to address the problems of public hospitals, the result of this study showed that delegate authorities to hospitals, decentralization, development of performance indicators could improved public hospital.…”
Section: Discussioncontrasting
confidence: 60%
“…This study is in line with previous studies that show a higher level of job satisfaction among general practitioners than among hospital doctors in Norway [ 6 - 8 ]. Norwegian health-care services were reformed in recent years with more cost- and consumer-based alternatives for hospital doctors provided by the Norwegian hospital reform of 2002 [ 25 , 26 ] and the establishment of a patient-list general practice outside of hospitals in 2001 [ 27 ]. A study in 2010 showed that these reforms had little impact on physician job satisfaction, and the article concluded that it seemed likely that physician job satisfaction was based more on internal values than external changes [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 39 cases were included in the study [ Figure 1 ]. [ 3 4 23 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 ] Reviewed evidence includes books and reports (3 cases) and scientific articles published in journals (36 cases).…”
Section: Resultsmentioning
confidence: 99%